Mitochondrial Structure and Polarity in Dendrites and the Axon Initial Segment Are Regulated by Homeostatic Plasticity and Dysregulated in Fragile X Syndrome - Bülow, Pernille; Wenner, Peter A.; Faundez, Victor; Bassell, Gary J. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial dysfunction has long been overlooked in neurodevelopmental disorders, but recent studies have provided new links to genetic forms of autism, including Rett syndrome and Fragile X Syndrome (FXS). Mitochondria show plasticity in morphology and function in response to neuronal activity and previous research has reported impairments in mitochondrial morphology and function in disease. We and others have previously reported abnormalities in distinct types of homeostatic plasticity in FXS. It remains unknown if or how activity deprivation triggering homeostatic plasticity affects mitochondria in axons and/or dendrites and whether impairments occur in neurodevelopmental disorders. Here, we test the hypothesis that mitochondria are structurally and functionally modified in a compartment specific manner during homeostatic plasticity using a model of activity deprivation in cortical neurons from wild type mice, and that this plasticity-induced regulation is altered in Fmr1 KO neurons. We uncovered dendritic specific regulation of mitochondrial surface area, whereas AIS mitochondria show changes in polarity; both responses are lost in the Fmr1 KO. Taken together our results demonstrate impairments in mitochondrial plasticity in FXS, which has not previously been reported. These results suggest that mitochondrial dysregulation in FXS could contribute to abnormal neuronal plasticity, with broader implications to other neurodevelopmental disorders and therapeutic strategies.